Therapeutic Effect of Calcimimetics on Osteoclast–Osteoblast Crosslink in Chronic Kidney Disease and Mineral Bone Disease - Kuo-Chin Hung (International Journal of Molecular Sciences, 2020)
We have previously demonstrated calcimimetics optimize the balance between osteoclastic bone resorption and osteoblastic mineralization through upregulating Wingless and int-1 (Wnt) signaling pathways in the mouse and cell model. Nonetheless, definitive human data are unavailable concerning therapeutic effects of Cinacalcet on chronic kidney disease and mineral bone disease (CKD-MBD) and osteoclast–osteoblast interaction. We aim to investigate whether Cinacalcet therapy improves bone mineral density (BMD) through optimizing osteocytic homeostasis in a human model. Hemodialysis patients with persistently high intact parathyroid hormone (iPTH) levels > 300 pg/mL for more than 3 months were included and received fixed dose Cinacalcet (25 mg/day, orally) for 6 months. Bone markers presenting osteoclast–osteoblast communication were evaluated at baseline, the 3rd and the 6th month. Eighty percent of study patients were responding to Cinacalcet treatment, capable of improving BMD, T score and Z score (16.4%, 20.7% and 11.1%, respectively). A significant correlation between BMD improvement and iPTH changes was noted (r = −0.26, p < 0.01). Nonetheless, baseline lower iPTH level was associated with better responsiveness to Cinacalcet therapy. Sclerostin, an inhibitor of canonical Wnt/β-catenin signaling, was decreased from 127.3 ± 102.3 pg/mL to 57.9 ± 33.6 pg/mL. Furthermore, Wnt-10b/Wnt 16 expressions were increased from 12.4 ± 24.2/166.6 ± 73.3 pg/mL to 33.8 ± 2.1/217.3 ± 62.6 pg/mL. Notably, procollagen type I amino-terminal propeptide (PINP), a marker of bone formation and osteoblastic activity, was increased from baseline 0.9 ± 0.4 pg/mL to 91.4 ± 42.3 pg/mL. In contrast, tartrate-resistant acid phosphatase isoform 5b (TRACP-5b), a marker of osteoclast activity, was decreased from baseline 16.5 ± 0.4 mIU/mL to 7.7 ± 2.2 mIU/mL. Moreover, C-reactive protein levels were suppressed from 2.5 ± 0.6 to 0.8 ± 0.5 mg/L, suggesting the systemic inflammatory burden may be benefited after optimizing the parathyroid–bone axis. In conclusion, beyond iPTH suppression, our human model suggests Cinacalcet intensifies BMD through inhibiting sclerostin expression and upregulating Wnt-10b/Wnt 16 signaling that activates osteoblastic bone formation and inhibits osteoclastic bone resorption and inflammation. From the perspective of translation to humans, this research trial brings a meaningful insight into the osteoblast–osteoclast homeostasis in Cinacalcet therapy for CKD-MBD.